Predictors of Diabetes Self-Management in Older Adults with Poorly Controlled Type 2 Diabetes Mellitus - Kanan, Piyawan; Piaseu, Noppawan; Malathum, Porntip; Belza, Basia (Pacific Rim International Journal of Nursing Research, 2019)
Poorly controlled type 2 diabetes, a complex phenomenon, is rapidly increasing particularly in older adults worldwide and in Thailand, the setting of this study. Effectiveness of diabetes self-management demands various factors supporting optimal outcomes. This descriptive correlational study examined the influences of ecological factors including gender, time since diagnosis, family history of type 2 diabetes mellitus, abdominal obesity, diabetes complications, health literacy, social networks, and social support on diabetes self-management. Through purposive sampling, the participants consisted of 166 older adults with poorly controlled type 2 diabetes mellitus at two hospitals in central Thailand province. Data were collected using questionnaires on the Functional, Communicative and Critical Health Literacy Scale, the revised Summary of Diabetes Self-Care Activities Scales, the Social Network in Adults Life, and the Diabetes Severity Complication Index; and nutrition assessment including waist circumference and HbA1c. Descriptive statistics and Stepwise Multiple Regression Analysis were used for data analysis. Results revealed that health literacy, abdominal obesity, time since diagnosis, and gender could together predict diabetes self-management, accounting for 14.7% of the variance. Prior to developing an effective intervention, an additional variable more specific to older adults needs to be examined such as self-efficacy that affects older adults’ confidence regarding health behavior modification. Nevertheless, these findings suggest approaches for nurses to promote diabetes self-management education that includes enhancing health literacy, and modifying health behaviors for control of abdominal obesity based on other health conditions, particularly in male older adults with type 2 diabetes mellitus.